Estrategias metodológicas y su influencia en la discalculia en los estudiantes de 2do año de E.G.B. de la U.E. Abdón Calderón Muñoz - Alvarado Torres, Melina (2023)
This final report is carried out by calculating the lines of research of the Technical University of Babahoyo in Education and Social Development, the line of the Faculty of Social Legal Sciences and Education in Human Talent and Teaching, in the line of research of the Basic Education Career in Inclusive Education and as a sub-line Methodological Strategies, therefore the report has as its theme: Methodological strategies and their influence on dyscalculia in second-year students of E.G.B. From the Abdón Calderón Muñoz Educational Unit. This report has the purpose of determining the importance and designing methodological strategies for the problem factor, dyscalculia. Well, in this area the student has many complications to recognize numbers, identify geometric figures and even solve basic mathematical operations and what better way to overcome the problem through games that arouse interest and curiosity for wanting to learn in a playful way . and active, it should be noted that students are more involved in learning if they are activities that arouse their attention. For this reason, the methodological strategies not only allow the acquisition of content, but also allow them to interact with different materials that facilitate the understanding of the subject, favor autonomy and at the same time benefit the interaction between peers, given that, when dealing with children of 2nd year of EGB, the teaching and learning process must be more dynamic, since the teacher must be very creative when designing and establishing the methodological activities that will be implemented in the classroom.